Daya Tarik Wisata Waduk Gunungrowo di Kabupaten Pati, Jawa Tengah - Sugiarto, Eko; Prasetyo, Kinanti Ida Nursanti (CV. ITTC INDONESIA, 2023)
Gunungrowo Reservoir in Sitiluhur Village, Gembong District, Pati Regency is one of the tourism destinations that is able to attract visitors with its tourist attractions. The purpose of this study is to identify and analyze the tourist attraction of Gunungrowo Reservoir both from the criteria and in terms of its relation to tourist activities. The theory used is the theory of tourist attraction. This research is a descriptive-qualitative. Primary data collection was done by observation and casual interview. Primary data collection was stopped when it reached the level of